Supply Chain Analysis Using Distribution Requirement Planning (DRP) Based On Bullwhip Effect Parameter (Case Study: Ud. Narwastu, Surabaya) - Hariastuti, Ni Luh Putu; Fardiya, Elia; Dwicahyani, Anindya Rachma (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2020)
Narwastu Firm is a company in Surabaya which produces traditional body care and aromatherapy. During the product distribution, this company encounters many mistakes such as inappropriateness between Purcashing Order (PO) from distributors/consumers and the goods delivered due to bullwhip effects. Therefore, this research aimed at reducing the bullwhip effects by implementing Collaborative, Planning, Forecasting, and Replenishment (CPFR) method and investigating a lot sizing technique for producing minimum distribution cost by Distribution Requirement Planning (DRP) method in order to regulate order and plan a certain distribution activity. The research results demonstrated that the bullwhip effect values after CPFR improvement of two products that could be repaired were 1.0 for Body Scrub Goats Milk Balibloom (BSC GM BB) 200 gr and 0.96 for Body Mist Sparkling White (BM SW) 60 ml. Meanwhile, the calculations by Distribution Requirement Planning (DRP) method with Economic Order Quantity (EOQ) method got the plans for ordering Body Scrub Lightening (BSC LIGHT) 200 gr by 182 times with total cost IDR 96,886,476 and Body Lotion Lightening (BL LIGHT) 250 ml by 235 times with total cost IDR 125,873,816.